Multilayer piezoelectret foam stack for vibration energy harvesting. (February 2017) - Ray, Chase A; Anton, Steven R
Electronic devices are high-demand commodities in today's world, and such devices will continue increasing in popularity. Currently, batteries are implemented to provide power to these devices; however, the need for battery replacement, their cost, and the waste associated with battery disposal present a need for advances in self-powered technology. Energy harvesting technology has great potential to alleviate the drawbacks of batteries. In this work, a novel piezoelectret foam material is investigated for low-level vibration energy harvesting. Specifically, piezoelectret foam assembled in a multilayer stack configuration is explored. Modeling and experimentation of the stack when excited in compression at low frequencies are performed to investigate piezoelectret foam for multilayer energy harvesting. An equivalent circuit model derived from the literature is used to model the piezoelectret stack. Two 20-layer prototype devices and one 40-layer prototype device are fabricated and experimentally tested via harmonic base excitation. Electromechanical frequency response functions between input acceleration and output voltage are measured experimentally. Modeling results are compared to experimental measurements to assess the fidelity of the model near resonance. Finally, energy harvesting experimentation in which the device is subject to harmonic base excitation at the fundamental natural frequency is conducted to determine the ability of the stack to successfully charge a capacitor. For a 20-layer stack excited at 0.5 g, a 100-µF capacitor is charged to 1.45 V in 15 min, and produces a peak power of 0.45 µW. A 40-layer stack is found to charge a 100-µF capacitor to 1.7 V in 15 min when excited at 0.5 g, and produce a peak power of 0.89 µW.